Formulasi Serbuk Wedang Tahu dan Pendugaan Umur Simpan Menggunakan Metode Kadar Air Kritis - Aliya Husna; Nurheni Sri Palupi; Feri Kusnandar; Azis Boing Sitanggang (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
Indonesia silken tofu dessert is a traditional dish made from silken tofu and ginger sauce. To enhance its shelf life, this study explored the development of silken tofu dessert into a powdered form. Traditionally, silken tofu is coagulated using calcium sulfate (CaSO₄), but there has been little research on the optimal concentration of CaSO₄ necessary for forming curd in powdered silken tofu comparable to the traditional version. This study aimed to identify the ideal concentration of CaSO₄ as a coagulant to be added to powdered silken tofu and to estimate its shelf life using the critical moisture method. Sensory testing was conducted to select the appropriate concentration of CaSO₄, comparing different levels to a control method. The results revealed significant differences between the powdered silken tofu dessert and the traditional counterpart. Among the three CaSO₄ concentrations tested (3, 5, and 7%), the dessert prepared with 3% CaSO₄ exhibited the closest resemblance to the traditional silken tofu dessert. A single serving of this powdered silken tofu dessert provides 125 kcal of total energy, accounting for 12% of the recommended daily allowance (RDA) for protein, 3% for total fat, and 6% for carbohydrates. When packaged in metallized plastic and stored at a relative humidity of 78% and a temperature of 30 °C, the shelf life of the powdered silken tofu dessert is extended up to 12 months.